Microsoft 365 Fundamentals (MS-900) - Gordon, Adam (Packt Publishing, 2024)
Dive into the world of Microsoft 365 with this detailed course designed for IT professionals and business users. Start with an overview of cloud computing fundamentals, including Software as a Service (SaaS), Infrastructure as a Service (IaaS), and Platform as a Service (PaaS). Learn how these services drive productivity in modern business environments. Transition into exploring the specific capabilities of Microsoft 365, such as core productivity tools like Office 365, Windows 365, and collaborative platforms like Teams, SharePoint, and Yammer. Understand hybrid and flexible working solutions, endpoint management, and the benefits of a Zero Trust security model. Each module builds your understanding, enabling you to manage and optimize Microsoft 365 within your organization. Progress into security and compliance features, covering identity and access management, threat protection, and data loss prevention. Gain detailed insights into Microsoft Defender, Secure Score, and compliance solutions to meet regulatory requirements and protect enterprise data. The course concludes with practical knowledge on licensing, service lifecycles, and support offerings, ensuring you have a comprehensive grasp of Microsoft 365's capabilities and benefits.